Targeting ferroptosis for improved radiotherapy outcomes in HPV‐negative head and neck squamous cell carcinoma - Joo Kyung Noh; Min Kyeong Lee; Yeonseo Lee; Minji Bae; Soonki Min; Moonkyoo Kong; Jung Woo Lee; Su Il Kim; Young Chan Lee; Seong‐Gyu Ko; Seon Rang Woo; Young‐Gyu Eun (Molecular Oncology)
To enhance the efficacy of radiotherapy (RT) in human papillomavirus (HPV)‐negative head and neck squamous cell carcinoma (HNSCC), we explored targeting ferroptosis, a regulated cell death process. We developed a gene signature associated with ferroptosis using Cox proportional hazard modeling in HPV‐negative HNSCC patients who underwent RT. This ferroptosis‐related gene signature (FRGS) was a significant predictor of overall survival and recurrence‐free survival in HPV‐negative HNSCC patients who received RT. Subtype B of the FRGS, characterized by decreased expression of ferroptosis inducers [nuclear receptor coactivator 4 (NCOA4) and natural resistance‐associated macrophage protein 2 homolog/divalent metal transporter 1 (NRAMP2/DMT1)] and increased expression of suppressors [phospholipid hydroperoxide glutathione peroxidase (GPX4) and ferritin heavy chain (FTH1)], was associated with poorer prognosis, potentially indicating the inhibition of ferroptosis. Furthermore, our in vitro and in vivo studies demonstrated that treatment with statins, such as atorvastatin and simvastatin, induced ferroptosis and sensitized radioresistant HNSCC cells to irradiation, improving radiosensitivity and potentially enhancing the response to RT. Additionally, in xenograft models, the combination of statins and RT led to a significant reduction in tumor initiation. These findings provide valuable insights for enhancing treatment and improving prognosis in HPV‐negative HNSCC by targeting ferroptosis and utilizing statins to sensitize tumors to RT‐induced cell death.